A randomised, double-blind, controlled efficacy trial of the LiESP/QA-21 vaccine in naïve dogs exposed to two leishmania infantum transmission seasons. - Gaetano Oliva; Javier Nieto; Valentina Foglia Manzillo; Silvia Cappiello; Eleonora Fiorentino; Trentina Di Muccio; Aldo Scalone; Javier Moreno; Carmen Chicharro; Eugenia Carrillo; Therese Butaud; Laurie Guegand; et al. (Public Library of Science (PLoS), 2014)
Canine leishmaniasis is an important zoonosis caused by uncontrolled infection with Leishmania infantum, where an inappropriate immune response is not only responsible for permitting this intracellular parasite to multiply, but is also responsible for several of the pathological processes seen in this disease. Effective canine vaccines are therefore a highly desirable prevention tool. In this randomised, double-blinded, controlled trial, the efficacy of the LiESP/QA-21 vaccine (CaniLeish, Virbac, France) was assessed by exposing 90 naïve dogs to natural L. infantum infection during 2 consecutive transmission seasons, in two highly endemic areas of the Mediterranean basin. Regular PCR, culture, serological and clinical examinations were performed, and the infection/disease status of the dogs was classified at each examination. The vaccine was well-tolerated, and provided a significant reduction in the risk of progressing to uncontrolled active infection (p = 0.025) or symptomatic disease (p = 0.046), with an efficacy of 68.4% and a protection rate of 92.7%. The probability of becoming PCR positive was similar between groups, but the probability of returning to a PCR negative condition was higher in the vaccinated group (p = 0.04). In conclusion, we confirmed the interest of using this vaccine as part of a comprehensive control program for canine leishmaniasis, and validated the use of a protocol based on regular in-depth assessments over time to assess the efficacy of a canine leishmaniasis vaccine.